Lipid-induced changes in intracellular iron homeostasis in vitro and in vivo. - Van Lenten, B J (1995)
Iron promotes cellular damage via its capacity to catalyze hydroxyl radical formation and by peroxidation of unsaturated lipids. The major cellular iron storage depot, ferritin, acts as a critical antioxidant defense by sequestering unbound or "free" iron, limiting its participation in damaging oxidative reactions. In this study, we investigated the relationship between LDL modified by artery wall cells and the regulation of intracellular free iron levels in the mouse model and in a human aortic endothelial and smooth muscle cell coculture system. We found in response to an atherogenic diet, fatty streak-resistant C3H/HeJ mice exhibited higher levels of liver apoferritin and lower intracellular concentrations of free iron than did fatty streak-susceptible C57 BL/6J mice. Also, ferritin repressor protein mRNA was not significantly suppressed after 15 wk on the atherogenic diet in female C57BL/6J mice, which exhibit the most extensive fatty streak formation, but was significantly reduced in C3H/HeJ mice. Iron loading of coculture cells resulted in elevations of cellular free iron and enhanced LDL-induced monocyte transmigration. Pretreatment of cells with apoferritin completely abolished iron-induced LDL modification. Addition of LDL to cocultures resulted in elevations in lipid peroxidation products, intracellular free iron, apoferritin mRNA expression, and apoferritin synthesis, suggesting a possible relationship between the oxidative modification of LDL and iron metabolism.